SOLIDIFICATION OF A356 ALLOY UNDER DIFFERENT DIRECTIONS AND MAGNITUDES OF STATIC ELECTRICAL FIELD - Basit, Sercan; Birinci, Semih; Marasli, Necmettin (SPRINGER INT PUBL AG, 2022)
A356 alloy, which is a commercial Al-Mg-Si alloy, was solidified with different magnitudes (0.42-1.25 kV cm(-1)) and directions of static electrical fields (E+: positive and E-: negative) to study the influences of E+ and E- on irregular interflake structure and mechanical property of Al-Mg-Si alloy. The direction of E is parallel or antiparallel to the solid-liquid (S-L) interface growth direction. The secondary dendrite arm spacing (lambda(2)), Al-alpha average grain surface area (S-alpha), sphericity ratio of Si into matrix (f(Si)) and Brinell hardness (HB) were measured for A356 alloy solidified with different E+ and E- values. The static electrical field force (F) affects the atomic mass flux at the S-L interface during the solidification and thus the microstructure, and physical and mechanical properties of the material are changed with E+ and E-. While the values of lambda(2), S-alpha and f(Si) increase with increasing the value of E-, the HB value decreases with increasing E-. However, the values of lambda(2), S-alpha and f(Si) decrease with increasing the E+ and the HB value increases with increasing E+. The relationships between them were determined with linear regression analysis. Graphic abstract Optical images of microstructure for the A356 alloy solidified with different directions and magnitudes of static electric fields; (a) 0.0 kV cm(-1) (b) 1.25 kV cm(-1) (c) - 1.25 kV cm(-1).
Keywords: solidification; electric field; A356 alloy; microstructure; hardness; sphericity ratio; MECHANICAL-PROPERTIES; ALUMINUM-ALLOY; HEAT-TREATMENT; SR; EVOLUTION; SILICON; GROWTH; CAST; Metallurgy & Metallurgical Engineering